Design and Development of a Project-Based Learning (PJBL) LMS to Improve the Competence of Junior Network Administrators among Grade XI Students at SMK Ketintang Surabaya - Akhdany Ichsar Al-Hamam; I Gusti Lanang Putra Eka Prismana (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Motivated by the low level of student participation and creative thinking skills in learning, as well as the suboptimal use of technology by teachers, this study aims to develop and examine the feasibility of a Project Based Learning (PjBL)-based Learning Management System (LMS) to improve the Junior Network Administrator competency in the Wired and Wireless Network Technology subject for Grade XI students at SMK Ketintang Surabaya. This study employs a Research and Development (R&D) method using the ADDIE model, which consist of the stages of analysis, design, development, implementation, and evaluation. The research subjects were divided into an ecxperimental class and a control class, with data collected through expert validation, learning outcome test, and questionnaires based on the Techmology Acceptance Model (TAM), including Perceived of Usefulness and Perceived Ease of Use variabels. The result indicate that the PjBL-based LMS has a very hugh validity level of 90.6% and is effective in significantly improving students’ learning outcomes, as shown by the difference in avarage scores between the control class (72.5) and the experimental class (87.1), as well as the Mann-Whitney U test result with a significance value of